Micromundo hipertextual & educação matemática - Silva, José Eduardo Ferreira da [UNESP] (2015)
This work, whose focus of interest is in the field of challenges posed by inserting the computer in the math teaching practice everyday, aims to present the development and implementation of a multirepresentacional electronic writing called 'micromundo hipertextual' to then, describe and analyze the data collected for the provision of this computational resource on the internet and, finally, present the project 'livro de areia' as an alternative proposal to the culture of the computer room, in other words, the trend to accommodate computers in an environment outside the classroom, usually deficient in the number of available machines that only reinforces the educational perspective that takes the computer as an end in itself and, therefore, makes the media its message. In short, it is a multidimensional research based on the thinking of Álvaro Vieira Pinto (1909-1987), which seeks to frame the relatively new fact of computer use during the daily math classroom in the structure of a process of thought and practical activity of work that exceeds its content at each stage of time, explains it and allows it to extract conclusions and reasonable projections